Communication in the family and children's deviant behavior in single parent families - Putri, Jasmine Safira Az'zahra; Nurwati, Nunung; Yunita, Desi (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2024)
Single parent families are form of incomplete family, where one parent is fully responsible for the education and character building of the child. This role vacancy often triggers deviant behavior in children. This study aims to explain communication and children's deviant behavior in single parent families. This research uses literature study research method with social deviation theory by Edwin H. Sutherland. There are several research results obtained from this study. First, the communication established in single parent families has not been effective. Second, the factors that cause children's deviant behavior in single parent families are caused by two things, namely disappointment with the situation in the family and the environment of peers who tend to behave deviantly. Third, the role of communication in preventing children's deviant behavior in single parent families is a major foundation in preventing children's deviant behavior. This study concludes that authoritative communication is the most appropriate application in single parent families to overcome communication problems in the family. Apart from that, good communication can have a significant impact on parents' relationships to be able to control and supervise children to prevent deviant behavior.